METHODOLOGY OF TEACHING ENGLISH - Mashrabova Nigora Mukhammadzakir kizi; Yuldasheva F. F. (Journal of new century innovations, 2022)
Abstract: This article provides information on English language teaching methodology and modern technologies used in English language teaching.